TREINAMENTO E ANÁLISE DA SATISFAÇÃO, MOTIVAÇÃO E COMPORTAMENTO EM UMA INSTITUIÇÃO PÚBLICA FEDERAL DE ENSINO SUPERIOR - Moreira, Sarah Tiburtino (2020)
In federal public institutions, there is a need to strengthen human resources policies, with a view to achieving better results. This is because the human resources of an institution are the main factors responsible for its success or failure, making it e